IDENTIFIKASI AKUIFER MENGGUNAKAN METODE GEOLISTRIK RESISTIVITAS DI DAERAH BEBANDEM, KARANG ASEM, BALI - Budy Santoso (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
Bungaya Kangin Village, Bebandem District, Karangasem Regency, Bali Province consists of paddy fields and settlements, required therefore a water source / aquifer that can meet all these needs. One of the Geophysical Methods that can identify the aquifer is the Geoelectric Method. Geoelectric method used in this research is Resistivity Method. Data acquisition using Vertical Electrical Sounding (VES) and Electrical Resistivity Tomography (ERT) Methods. VES method is a method of measurement to determine the variation of resistivity vertically at one point. Electrical Resistivity Tomography (ERT) method is a method of measuring resistivity on soil surface / rock by using many electrode (51 electrode), to obtain sub-surface resistivity variation lateraly and verticaly, to obtain sub-surface image. The equipment used for geoelectric measurements is Resistivity Meter of Naniura NRD 300 Hf which has been equipped with a switchbox to adjust the displacement of 51 electrodes. Based on the resistivity modeling results, the aquifers in the study area were found in rough sandstones with resistivity values : (49 - 100) Ohm.m.